Identification of N, P, and K in Solid Waste from Palm Flour Production and Their Benefits as Organic Compost Fertilizer Ingredients - Izzawati, Zain; Hanik, Nur Rokhimah; Wiharti, Tri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The palm flour manufacturing industry produces a lot of liquid waste and solid waste. The absence of a waste processing system means the waste is dumped around the production house. The large amount of solid waste that is dumped every day causes a buildup of waste on riverbanks. The flow of river water is disturbed, pollutes the river ecosystem, and the smell is unpleasant. The research aims to identify the content of N, P, and K elements in palm flour solid waste. The data obtained will be used as a basic reference for using palm flour solid waste as an alternative compost material considering that most of the Pucang Miliran village area is an agricultural area. The research was carried out by taking a sample of 1 kg of sugar palm flour solid waste and testing it for the content of N, P, and K. Data from laboratory tests were analyzed descriptively supported by a literature study. The research results showed that palm flour solid waste contained Nitrogen (N) of 194.227 mg/Kg, Phosphorus (P) of 410.270 mg/Kg, and Potassium (K) of 832.382 mg/Kg. The presence of the three nutrients N, P, and K in large enough quantities can be considered that palm flour solid waste can be a good alternative material for making organic fertilizer/compost. Further research is needed to determine the comparison and combination of various compost material compositions to produce the best palm solid waste compost.